Analysing ULMWP’s Online Propaganda Strategy Through Hank Prunckun’s ICV Framework - Simamora, Nober Naung; Riyanta, Stanislaus; Masithoh, Nidia (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2025)
This study explores how the United Liberation Movement for West Papua (ULMWP) uses digital communication to promote Papua independence narratives and gain attention in international forums. Drawing on Prunckun’s Threat Analysis Theory (2015), this research examines ULMWP’s online propaganda strategies by assessing its intent, capability, and the vulnerabilities it targets. Using an explanatory qualitative method, data were collected from interviews with practitioners and secondary sources published between 2019 and 2023. The findings show that ULMWP consistently works to build global support while undermining Indonesia’s legitimacy through emotionally charged narratives focused on injustice and human rights. These efforts are implemented through coordinated digital activism and proactive engagement with international media, while uses a diplomatic mechanism. According to Ring’s Threat Level Classification (2009), ULMWP’s efforts fall between serious and critical categories given their impact on public perception and foreign policy challenges. The study suggests that stronger intelligence strategies are needed to maintain national cohesion in the digital era.